CHECHNIA—THE OSCE EXPERIENCE 1995-2003 - Gunnar SKAGESTAD, Odd (CENTRAL ASIA AND THE CAUCASUS, 2008)
Gradually evolving from the embryonic détente initiatives of the 1970s, and having braved the Charybdian rocks of the still lingering Cold War of the 1980s, the Organization for Security and Cooperation in Europe (OSCE) finally emerged as a full-fledged international organization with the renaming in 1995 of what had previously been known as The Conference for Security and Cooperation in Europe (CSCE). On its website, the OSCE now boasts of being “the world’s largest regional security organization whose 55 participating States span the geographical area from Vancouver to Vladivostok.”1 The objectives of the OSCE are, broadly speaking, concerned with early warning, conflict prevention and post-conflict rehabilitation. Its listing of activities also includes such tasks as antitrafficking, arms control, border management, combating terrorism, conflict and democratization. The OSCE’s main tools in carrying out these tasks are its field operations. Acting under the directions from the OSCE Secretariat in Vienna, and under the general auspices of the organization’s Chairman-in-Council, the field operations comprise a number of rather diverse groups—each one with a specific mandate according to the problem(s) to be addressed in their respective operational areas. At the time of the writing (February 2008), the OSCE maintains 19 field operations in SouthEastern Europe, Eastern Europe, the Caucasus and Central Asia. These are the following: OSCE Presence in Albania OSCE Mission to Bosnia and Herzegovina OSCE Mission to Croatia OSCE Mission to Serbia and Montenegro OSCE Mission in Kosovo OSCE Spillover Monitor Mission to Skopje OSCE Office in Minsk OSCE Mission to Moldova OSCE Project-Coordinator in Ukraine OSCE Office in Baku OSCE Mission to Georgia OSCE Office in Erevan